Komposisi Nutrien dan Mineral Silase Sabut Kelapa Muda pada Berbagai Level Penambahan Dedak Padi - Narek, Emilia Martha; Un, Floriana Petrosa; Koten, Bernadete Barek; Wea, Redempta; Aoetpah, Aholiab (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Abstract The objective of this study was to evaluate minerals and nutrient composition of young coconut husk silage fermented with rice bran at different concentrations. The study was conducted for seven months in the Laboratory of Feed Technology of State Agricultural Polytechnic of Kupang. A completely randomised design was employed with four treatments and five replicates. The treatments were young coconut husk without rice bran (P0) or the husk plus 4% (P1), 8% (P2) or 12% (P3) of rice bran out of the silage total weight. Variables measured were dry matter, ash, crude protein, crude lipid, crude fibre, Calcium, Potassium and Phosphorus. Analysis of variance showed that rice bran significantly (P<0.01) affects all variables measured. The Duncan’s range multiple test showed that 12% and 4% were the best rice bran concentrations to increase nutrient content and minerals of the silage, respectively. It can be concluded that adding 12% of rice bran to young coconut husk silage increased dry matter, ash, crude protein and crude lipid but reduced Calcium and Potassium. Crude fibre and Phosphorus increased at the inclusion of 8% rice bran. Key words: Nutrient; Minerals; Rice bran; Silage; Young coconut husk. Abstrak Penelitian yang bertujuan untuk mengevaluasi komposisi nutrien dan mineral silase sabut kelapa muda pada berbagai level penambahan dedak padi, telah dilaksanakan selama 7 bulan di Laboratorium Teknologi Pakan Politeknik Pertanian Negeri Kupang, dengan menggunakan rancangan acak lengkap dengan 4 perlakuan yang terdiri dari P0 : sabut kelapa muda tanpa dedak padi, P1 : sabut kelapa muda + 4% dedak padi, P2 : sabut kelapa muda + 8% dedak padi, P3 : sabut kelapa muda + 12% dedak padi dengan 5 kali ulangan. Variabel yang diukur adalah kadar bahan kering (BK), kadar abu, kadar protein kasar (PK), kadar lemak kasar (LK), kadar serat kasar (SK), kadar kalsium (Ca), kadar kalium, dan kadar fosfor. Analisis ragam menunjukkan bahwa level dedak padi yang berbeda berpengaruh sangat nyata (P<0,01) terhadap kadar BK, kadar abu, kadar PK, kadar LK, kadar SK, kadar Ca, kadar K, dan kadar P. Uji Duncan memperlihatkan level dedak 12% menghasilkan nutrien terbaik dan level 4% menghasilkan kadar mineral terbaik. Disimpulkan bahwa penambahan level dedak padi hingga 12% dapat meningkatkan kadar BK, kadar abu, kadar PK, dan kadar LK. tetapi menurunkan kadar Ca dan kadar K. Kadar SK dan P meningkat hingga penambahan level dedak padi 8%. Kata kunci : Dedak padi; Kadar nutrient; Kadar mineral; Silase; Sabut kelapa muda.